The Risk Factors of Pancreatic Cancer Patients in Dr. Cipto Mangunkusumo National Hospital, Jakarta During 2014-2019 - Kaka Renaldi; Teddy Septianto; Dadang Makmun (The Indonesian Journal of Gastroenterology, Hepatology, and Digestive Endoscopy, 2020)
Background: Pancreatic cancer is a very rare cancer with age-adjusted rates ranging from about 5 to 10 new cases per 100,000 persons per year. It has one of the worst prognoses of any type of cancer, with a 5-year survival rate of only 4.6%. Several risk factors have been identified, including older age, smoking, familial history of pancreatic cancer, obesity, chronic pancreatitis, diabetes mellitus, and alcohol consumption.Method: This was a descriptive study describing the risk factors of patients who were diagnosed with pancreatic cancer in the period between 1 January 2014 – 1 January 2019 at the Cipto Mangunkusumo National Referral Hospital (RSCM) Jakarta. Data were obtained from the medical records and Endoscopic Retrograde Cholangiopancreatography (ERCP) database from the RSCM Gastrointestinal Endoscopy Center.Results: From January 2014 to January 2019 there were 123 patients with newly diagnosed pancreatic cancer in RSCM. The mean age was 52 years old. The incidence of pancreatic cancer is more common in men (53%) than women (47%). The most common risk factor identified is smoking which was found in 29% of patients, followed by obesity at 27.9% and a history of diabetes mellitus at 19.5%. Risk factors with a fairly low prevalence include alcohol consumption at 9.7% and chronic pancreatitis at 2.4%. No family history of pancreatic cancer is identified in any subject.Conclusion: Smoking, obesity, and diabetes mellitus are common risk factors in pancreatic cancer patients. In contrast, chronic pancreatitis, alcohol consumption, and family history of pancreatic cancer are less commonly identified in patients.